From horticulture and biofuel to invasion: the spread of Miscanthus taxa in the USA and Europe. (13th February 2015) - Schnitzler, A; Essl, F; Bohren, Christian
Summary Species of the genus Miscanthus (Poaceae) have recently become widely planted for ornamental and industrial uses. Yet these large perennial grasses have several traits that suggest a high invasion potential. To inform the debate on the benefits and risks of introducing these new biofuel crops, this publication summarises the invasion of Miscanthus species in Europe and the USA. Databases from North America were interrogated, and occurrence data from a variety of European sources were examined. In both continents, M. sinensis and M. sacchariflorus have recently spread rapidly, although invasion started earlier in the USA and both species are more widespread there. Both species mostly colonise grasslands and ruderal habitats. In addition, some escapes of the hybrid M. × giganteus, which has a particularly strong invasion potential because of its vigorous growth and greater capacity to establish in cool climates, have already been recorded. We conclude that the invasion potential of Miscanthus species needs to be thoroughly tested, the incipient invasions in Europe and the USA monitored and, if required, planting restrictions should be adopted.